Charisma and Capitalism in Motion: the Continuing Relevance of Robert P. Weller’s Ideas for Indonesian Islamic Modernity - Roberto Arieza Martin Purba; Dody S. Truna; Rifki Rosyad (Sean Institute, 2026)
This study examines Robert P. Weller’s theoretical contributions to understanding the relationship between religious transformation and the capitalist economic system in Asia. Weller challenges the Weberian secularization paradigm by proposing a dialectical model of secularization–religionization and a typology of three religious responses to capitalism: embracing amorality, prosperity theology, and philanthropic amelioration. Through empirical studies in Taiwan, he demonstrates that religion is not a victim of modernity but a moral actor negotiating global economic values. This review evaluates Weller’s theoretical framework, methodological approach, empirical contributions, as well as its limitations and directions for future research.